Tailoring the Plasmonic Modes of a Grating‐Nanocube Assembly to Achieve Broadband Absorption in the Visible Spectrum. (26th August 2014) - Geldmeier, Jeffrey; König, Tobias; Mahmoud, Mahmoud A.; El‐Sayed, Mostafa A.; Tsukruk, Vladimir V.
<x xml:space="preserve">Abstract</x> Engineered metal‐dielectric‐metal nanostructures with broadband absorbing properties in the visible spectral range are fabricated by combining the plasmonic resonances of different noble metal nanostructures. Silver nanocubes and gold nanogratings couple to each other using a dielectric polymer spacer with controllable thickness, resulting in a large multiplicative enhancement of absorption properties across a broad spectral range. Narrow, long nanogrooves in a gold film are first fabricated using electron beam lithography, after which a polymer spacer layer with a controllable thickness ranging from 4 to 12 nm is assembled by spin‐assisted layer‐by‐layer assembly. Finally, silver nanocubes with different surface coverages ranging from 12% to 22% are deposited using the Langmuir–Blodgett technique. The individual plasmon resonances of these different nanostructures are located at significantly different optical frequencies and are tuned in this study to allow a significant increase of light absorbance of the original gratings to an average value of 84% across the broad wavelength range of 450–850 nm.